Tahanan a family building program to be utilized by Atikha Overseas Workers and Communities Initiative, Inc. to empower OFW children aged 9-12 and their parents taking on physical separation from one another - Icay, Kathleen Anne Y.; Aguilar-Reyes, Mitzi Marie (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
As 2.2 million Filipinos leave the country each year in search of overseas work, the OFW (Overseas Filipino Worker) phenomenon remains to be a prevailing force in Philippine society. Yet behind the glittering image of being modern-day heroes and spear heads of the national economy, families are being separated from each other and children are left behind on a daily basis, threatening to create an emotional gap among OFW family members. Government and Non-Government Organization alike were established specifically for the wellbeing of OFW families. (e.g. Commission on Filipino Overseas (CFO), Overseas Workers Welfare Administration (OWWA), the OFW Family Club). However, they fail to address the effects of their migration to loved ones left behind. Services offered by these institutions focus on departure and employment technicalities, and pay little to no attention to the emotional cost of physical separation among OFW families. In response to this, Atikha Overseas Workers and Communities Initiative, Inc. (Atikha), a non-government organization geared towards addressing the emotional cost of migration to OFWs and their families, developed the School-Based Program for Children of Overseas Filipinos in 2009. Alongside the Department of Education (DepEd) in Laguna, they created activity-based lesson plans that integrate financial literacy and migration issues in the curriculum of elementary and secondary education of schools with the highest number of OFW children in the area, in the form of a four day school-based program. However, trhough conducted interviews and observational research, the visual communicator identifies the program's weak points: First, it is short-lived, starting and ending only within its allotted period of four days; Second, the program does not have follow through efforts to sustain lessons communicated during activities, missing to ensure a lasting impact on participants; Third, though family building is an effort that requires the participation from all sides of the family, the program is one-way, working only with the children and not with their OFW parents; Fourth, the program is strictly confined within the limits of its target schools, having no means to reach children not currently enrolled in their systems; and lastly, the program lacks visual materials, heavily relying instead on the children's outputs to carry out activities. Hence, this project aims to contribute to addressing the emotional cost of migration to OFW children and their parents through a Family Building Program. To be utilized by Atikha, the visual communicator proposes a 7 week family building program that utilizes an animated short film with follow-through workshop activities as a platform and a strategy to deliver and continually impart its objectives. Through this, the visual communicator aims to grant OFW children the representation in visual media that they deserve but do not have; to improve the quality of the relationship among OFW family members--and through contributing to the well-being of the Filipino family, the most basic foundation of society, this project aims to partake in contributing to the betterment of Philippine society as a whole. Though most importantly, the visual communicator aims to express that physical separation does not entail emotional distance. Physical proximity is not the only standard bu which to measure love. No matter wherever you are or how far you go, home is always with you.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 205-207.
Keywords: Filipinos -- Employment -- Foreign countries